Characterization and Comparative Analysis of Olfactory Receptor Co-Receptor Orco Orthologs Among Five Mirid Bug Species - Wang, Qi; Wang, Qian; Zhou, Yan-Le; Shan, Shuang; Cui, Huan-Huan; Xiao, Yong; Dong, Kun; Khashaveh, Adel; Sun, Liang; Zhang, Yong-Jun (Frontiers in Physiology, 2018)
The phytophagous mirid bugs of Apolygus lucorum, Lygus pratensis as well as three Adelphocoris spp., including Adelphocoris lineolatus, A. suturalis and A. fasciaticollis are major pests of multiple agricultural crops in China, which have distinct geographical distribution and occurrence ranges. Like many insect species, these bugs heavily rely on olfactory cues to search preferred host plants, thereby investigation on functional co-evolution and divergence of olfactory genes seems to be necessary and is of great interest. In the odorant detection pathway, olfactory receptor co-receptor (Orco) plays critical role in the perception of odours. In this study, we identified the full-length cDNA sequences encoding three putative Orcos (AsutOrco, AfasOrco and LpraOrco) in bug species of A. suturalis, A. fasciaticollis and L. pratensis based on homology cloning method. Next, sequence alignment, membrane topology and gene structure analysis showed that these three Orco orthologs together with previously reported AlinOrco and AlucOrco shared high amino acid identities and similar topology structure, but had different gene structure especially at the length and insertion sites of introns. Furthermore, the evolutional estimation on the ratios of non-synonymous to synonymous (Ka/Ks) revealed that Orco genes were under strong purifying selection, but the degrees of variation were significant different between genera. The results of quantitative real-time PCR experiments showed that these five Orco genes had a similar antennae-biased tissue expression pattern. Taking these data together, it is thought that Orco genes in the mirid species could share conserved olfaction roles but had different evolution rates. These findings would lay a foundation to further investigate the molecular mechanisms of evolutionary interactions between mirid bugs and their host plants, which might in turn contribute to the development of pest management strategy for mirid bugs.